Pengaruh Luas Lahan, Tenaga Kerja dan Pupuk Terhadap Hasil Produksi Karet di Desa Sungai Bokor Kecamatan Mataraman Kabupaten Banjar - Apriyanti, Novi (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
Each rubber farmer has different results. Several factors influence thedifference. In the production process, the output is strongly influenced by these inputs,in which the context between the production and information is described in theproduction function. The purpose of this research is to see the effect of land area,labor, and fertilizer on rubber production. The research uses primary and secondary data, which is quantitativeresearch. Sampling amounted to 64 farmers. Data collection techniques using aquestionnaire, in-depth interviews, and observation. Analysis technique using theCobb-Douglas function that has been transformed into a natural logarithm that isusing multiple regression. And the result of this study is the land area(X1), labor(X2), and fertilizer(X3).Simultaneously affect the production of rubber(Y). But partially only the size of landinvolving the production of rubber. In this study, the significant and most dominantproduction factors affect the rubber production in Sungai Bokor, Mataraman, BanjarIs Land Area.